Effectiveness of Platelet-Rich Plasma in the Treatment of Androgenic Alopecia Compared to Placebo and Topical Minoxidil: A Systematic Review - Julia Maria Borowiecka; Bartosz Dalewski; Łukasz Pałka (MDPI AG, 2022)
Platelet-rich plasma (PRP) has become an increasingly popular alternative or additional method in treating androgenic alopecia (AGA). AGA is a multifactorial disease, in which testosterone plays a significant role in influencing hair growth. The aim of this study was to evaluate the effectiveness of PRP treatment in AGA affecting men and women. The research was performed using the following databases: PubMed, Embase, and Cochrane Library. The effects were measured with a TrichoScan by comparing the initial and final hair density. A significant difference was observed between the areas of the scalp where PRP injections were made and those where saline was administered. Compared to conventional minoxidil 5% topical PRP, PRP is more effective in treating alopecia. A beneficial outcome of combined therapy with PRP and minoxidil 5% was observed. Therefore, PRP is not only an excellent alternative for patients in whom the minoxidil 5% topical monotherapy did not bring the expected effects or who experienced unacceptable side effects, but can also be used as a complementary therapy.